Legal Foundations of the Human Right to Peace - Villan-Duran, Carlos (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2013)
While most developed States refuse accepting the concept of human right to peace, developing States support civil society organizations’ contribution to the codification and progressive development of the emerging human right to peace. This study focuses on the strong legal foundations of the human right to peace in international human rights law. Therefore, developed States should listen to other States and civil society organizations and join the ongoing codification process of the human right to peace at the UN Human Rights Council.

Podczas gdy najbardziej rozwinięte państwa odmawiaj¹ uznania koncepcji prawa człowieka do pokoju, państwa rozwijające się wyrażają poparcie dla wkładu organizacji pozarządowych w proces kodyfikacji i rozwoju prawa człowieka do pokoju. Niniejsze studium ukazuje prawne podstawy omawianego uprawnienia w ramach międzynarodowego prawa praw człowieka. Z tego względu, Autor postuluje, aby państwa rozwinięte przychyliły się do stanowiska krajów rozwijających się i organizacji pozarządowych, wspierając proces kodyfikacji prawa człowieka do pokoju w ramach Rady Praw Człowieka ONZ.
Prawne podstawy prawa człowieka do pokoju